MORPHOMETRY AND MORPHOGENESIS OF IRON-MANGANESE NODULES - Goryainov I.N.; Kazakova V.Y.; Kulikov A.N.; Motychko V.V.; Rumyantsev S.N.; Smirnova L.S. (My University, 1988)
This article discusses the shape characteristics of iron-manganese nodules and their dependence on the chemical composition and growth rate of the nodules. A sample of length of three axes for 609 nodules from the Clarion-Clipperton nodule province of the Pacific Ocean was constructed and, the statistical correlations between these properties was determined: the average length of the short axes of the nodules, corresponding to specific lengths of the long and intermediate axes; the multiple correlation coefficient; and the partial correlation coefficient. Based on these equations and other derivations, growth rate, chemical composition, and dimensions of nodules are determined, along with paired, partial, and multiple coefficients of correlation between growth rate of nodules and concentrations of Fe and Mn, and other aspects of the subject.